Для вас, женщины: альманах ([главный редактор О. Н. Пилюгин]) - Пилюгин Олег Николаевич (2016)
Экземпляры: БС (20161026) / Инвентарный номер: РТШ54457 / Сис.шифр: 37.279 / Авт.знак: Д 52 / ГРНТИ: 75.35 / ББК: 37.279